Advances in Alzheimer's and Parkinson's Disease Insights, Progress, and Perspectives - Fisher, Abraham.; Fisher, Abraham.; Memo, Maurizio.; Memo, Maurizio.; Stocchi, Fabrizio.; Stocchi, Fabrizio.; Hanin, Israel.; Hanin, Israel. (Advances in Behavioral Biology,, 2008)
Proceedings of the 7th International Conference on Alzheimer’s Disease and Parkinson’s Disease (ADPD), held March 9-13, 2005 in Sorrento, Italy. The subject matter of the ADPD conferences is unique in that it deals not only with issues related individually to Alzheimer’s disease and Parkinson’s disease, but also with the integration of these and other related diseases. The most up-to-date techniques and research findings are illustrated in this volume, covering topics such as immunology, neuroscience, pharmacology, genetics, molecular biology, biochemistry and the history, epidemiology, clinical phenomenology, diagnosis, imaging, treatment ,and future perspectives of Alzheimer’s and Parkinson’s Diseases.